Los contrarios - Candell, Arianna; Rovira, Francesc (Hauppauge, NY Barron's Educational Series, 2004)
Learn about opposites with colorful illustrations.
Keywords: Spanish language -- Synonyms and antonyms -- Juvenile literature; Spanish language materials -- Juvenile literature